Phosphine-Free [3+2] Cycloaddition of Propargylamines with Dialkyl Azodicarboxylates: An Efficient Access to Pyrazole Backbone - Zhang, Yicheng; Liu, Jie; Jia, Xueshun (Synthesis, 2018)
A phosphine-free [3+2] cycloaddition reaction of the substituted propargylamines with dialkyl azodicarboxylates at room temperature is described. This reaction provides a new approach to functionalized pyrazoles in good yields and high selectivity.
Keywords: propargylamine; dialkyl azodicarboxylates; cycloaddition; pyrazole; phosphine-free